ceRNA crosstalk mediated by ncRNAs is a novel regulatory mechanism in fish sex determination and differentiation - Tang, Lili; Huang, Fei; You, Wuxin; Poetsch, Ansgar; Nóbrega, Rafael Henrique [UNESP]; Power, Deborah Mary; Zhu, Tengfei; Liu, Kaiqiang; Wang, Hong-Yan; Wang, Qian; Xu, Xiwen; Feng, Bo; et al. (Cold Spring Harbor Laboratory, 2022)
Competing endogenous RNAs (ceRNAs) are vital regulators of gene networks in mammals. The involvement of noncoding RNAs (ncRNAs) as ceRNA in genotypic sex determination (GSD) and environmental sex determination (ESD) in fish is unknown. The Chinese tongue sole, which has both GSD and ESD mechanisms, was used to map the dynamic expression pattern of ncRNAs and mRNA in gonads during sex determination and differentiation. Transcript expression patterns shift during the sex differentiation phase, and ceRNA modulation occurs through crosstalk of differentially expressed long ncRNAs (lncRNAs), circular RNAs (circRNAs), microRNAs (miRNAs), and sex-related genes in fish. Of note was the significant up-regulation of a circRNA from the sex-determining gene dmrt1 (circular RNA dmrt1) and a lncRNA, called AMSDT (which stands for associated with male sex differentiation of tongue sole) in Chinese tongue sole testis. These two ncRNAs both share the same miRNA response elements with gsdf, which has an up-regulated expression when they bind to miRNA cse-miR-196 and concurrent down-regulated female sex-related genes to facilitate testis differentiation. This is the first demonstration in fish that ceRNA crosstalk mediated by ncRNAs modulates sexual development and unveils a novel regulatory mechanism for sex determination and differentiation.